A mixed-integer LP model for the optimal allocation of voltage regulators and capacitors in radial distribution systems - Franco, John F. [UNESP]; Rider, Marcos J. [UNESP]; Lavorato, Marina [UNESP]; Romero, Rubén [UNESP] (Elsevier, 2013)
This paper presents a mixed-integer linear programming model to solve the problem of allocating voltage regulators and fixed or switched capacitors (VRCs) in radial distribution systems. The use of a mixed-integer linear model guarantees convergence to optimality using existing optimization software. In the proposed model, the steady-state operation of the radial distribution system is modeled through linear expressions. The results of one test system and one real distribution system are presented in order to show the accuracy as well as the efficiency of the proposed solution technique. An heuristic to obtain the Pareto front for the multiobjective VRCs allocation problem is also presented. © 2012 Elsevier Ltd. All rights reserved.
Keywords: Distribution system optimization; Mixed-integer linear programming; Optimal allocation of voltage regulators and capacitor; Allocation problems; Distribution systems; Linear expression; Mixed integer linear programming; Mixed-integer; Multi objective; Optimal allocation; Optimality; Optimization software; Pareto front; Radial distribution systems; Real distribution; Solution techniques; Steady-state operation; Switched capacitor; Test systems; Capacitors; Integer programming; Optimization; Voltage regulators; Local area networks